Quantitative determination of stone fragmentation efficiency - Teo, Henry Keng Hiang. (2013)
The occurrence of kidney stone had been increasing over the years, with possibilities due to poor dietary habits of people. This medical condition is not life threatening, however, affects ones daily life and has to be treated before other complication arise. Treatment for kidney stones may exist in three different forms; Surgery, Extracorporeal Shock Wave Lithotripsy (ESWL) and Percutaneous Ultrasound Nephrolithotomy (PNL). The main focus of study for this report is on ESWL, where its working principles will be further discussed in detail. The three major chapters are construction of test-rig, stone phantom module design and experimentation, and numerical study of echo analysis. The entire design process of the test-rig will be shown in the construction of test-rig, where design of stone phantom module along with fabrication of stone phantom is provided in chapter 4. There is also a need to better identify the kidney stones within the kidney to ensure a more effective treatment process, a study of echo analysis is conducted in chapter 5. The report will finally be concluded with work done so far and suggestions for future work.